Floridian Consumer Perceptions of Local Versus Organic Ornamental Plants - Hayk Khachatryan; Alicia Rihn (EDIS)
Horticultural consumers in Florida are interested in local and organically produced plants. But these terms can mean different things in different regions. UF/IFAS researchers conducted a survey last summer which suggests that consumers in central Florida define local as plants that are grown near where they are sold and identify the most important local benefits as product safety, quality, and community support. Organic plants are perceived as requiring fewer chemical additives and being healthier for the environment. The importance of these traits varies by plant type. This 5-page fact sheet was written by Hayk Khachatryan and Alicia Rihn, and published by the UF Department of Food and Resource Economics, April 2015.